Supervised Physical Activity Interventions In The Management Of Cancer-Related Fatigue: A Systematic Review (2014)
Metodology: Systematic review of randomized controlled trials. Adults (>20 years old) diagnosed with any type of cancer regardless of treatment or diagnosis stage. Physical activity interventions (aerobic and resistance training) supervised by health professionals. CRF was the primary outcome measure, whilst secondary outcomes included depression, the comparison between supervised and non-supervised interventions, physical and functional wellbeing. Risk of bias and methodological quality were evaluated using the PEDro scale.Background: Cancer-related fatigue is the most common and distressing symptom among cancer survivors; physical activity has been proposed as a safe and effective intervention to control it. Objective: This study aimed to determine the effectiveness of supervised physical activity interventions for the management of cancer-related fatigue (CRF).Results: Fourteen studies (n=14) were included (n=1638) with low risk of bias (PEDro mean score=6,5±1). Supervised physical activity significantly improved CRF; similar results were found for resistance training. Further, supervised physical activity was more effective than conventional care for improving CRF among breast cancer.Conclusion: Supervised physical activity interventions provide an overall reduction on CRF. These findings suggest that guidelines of aerobic and resistance training should be included in oncologic rehabilitation programs. © 2014, Grupo Aula Medica S.A. All rights reserved.